Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5195/jmla.2022.1280
|View full text |Cite
|
Sign up to set email alerts
|

Retracted publications in pharmacy systematic reviews

Abstract: Objective: Systematic reviews and other evidence syntheses, the pinnacle of the evidence pyramid, embody comprehensiveness and rigor; however, retracted data are being incorporated into these publications. This study examines the use of retracted publications in the field of pharmacy, describes characteristics of retracted publications cited by systematic reviews, and discusses factors associated with citation likelihood.  Methods: Using data from Retraction Watch, we identified retracted publications in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
0
17
1
2
Order By: Relevance
“…The range and frequency of retraction reasons varied between different academic fields. For example, in both dentistry and obstetrics, redundant publications, and plagiarism were the most common reasons ( 27 , 46 ), while in the field of pharmacy, falsification, or data manipulation were the most frequent ( 47 ), which are in contrast to our findings in schizophrenia-related research. The development and application of Plagiarism Detection software, such as iThenticate and Turnitin ( 16 , 46 ), may contribute considerably to preventing plagiarism issues.…”
Section: Discussioncontrasting
confidence: 99%
“…The range and frequency of retraction reasons varied between different academic fields. For example, in both dentistry and obstetrics, redundant publications, and plagiarism were the most common reasons ( 27 , 46 ), while in the field of pharmacy, falsification, or data manipulation were the most frequent ( 47 ), which are in contrast to our findings in schizophrenia-related research. The development and application of Plagiarism Detection software, such as iThenticate and Turnitin ( 16 , 46 ), may contribute considerably to preventing plagiarism issues.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent evidence suggests that systematic reviews and meta-analyses mis-cite retracted studies at problematic levels and may not be immune to the impacts of some retractions. One study focusing on the citation of retracted publications in pharmacy systematic reviews found that 20% of the retracted publications in a sample had been cited in systematic reviews, and that approximately one third of those citations had occurred after the retraction of the publication [31]. Of these post-retraction citations, 80% did not indicate that the publication had been retracted [32].…”
Section: The Problemmentioning
confidence: 99%
“…This lengthiness has implications for the use of the material. For example, retracted pharmacy publications cited in systematic reviews were retracted 7 years after initial publication, whereas retracted pharmacy publications that were not cited in systematic reviews were retracted 3.2 years after publication [31]. Retractions may sometimes be preceded by an expression of concern, which aims to alert readers to a potential problem but does not definitively state that the publication or its findings are flawed.…”
Section: Why Is a Publication's Retracted Status Often Not Acknowledg...mentioning
confidence: 99%
“…This is important given that the issues discussed in the systematic review manuscript may be similar to those in the included primary studies. 11 You may be able to carry out an electronic plagiarism check to ensure that the similarity index is acceptably low before the manuscript is submitted for publication. 12 Paraphrasing and using quotations with references to the original sources protect against allegation of plagiarism.…”
Section: Introductionmentioning
confidence: 99%